Antimicrobial Activity and Acute Toxicity of Choline Based Ionic Liquid Mixtures. (2019) - Ul Hassan Shah, Mansoor; Moniruzzaman, Muhammad; Mahabubur Rahman Talukder, Md.; Bt Yusup, Suzana
Abstract: Chemical dispersants are globally accepted response option for marine oil spill remediation. However, their toxicity reduces its employment in sea environment. To address this limitation, the use of environmentally benign dispersants is the best possible approach. In this research, the antimicrobial activity and fish toxicity of environmentally benign dispersants comprise of binary mixture of choline based ionic liquids, i-e; choline myristate ([Cho][Mys]) and choline oleate ([Cho][Ol]) using water as a solvent were investigated to ensure their safe use in marine environment. The antimicrobial activity at their 50% effective concentrations (EC50 ) against Gram-positive and -negative bacteria illustrates that all the mixed binary system can be classified as "practically harmless". The half-lethal concentration, LC50 on zebra fish ( Danio rerio ) also revealed that the studied mixed surfactant system could be ranked as 'non-toxic'. The results presented in this research indicates that the dispersant comprise of binary mixture of [Cho][Mys] and [Cho][Ol] could potentially replace the toxic marine spill dispersants